Pregnant women exercise at a higher intensity during 30 min of self-paced cycling compared with walking during late gestation: Implications for 2 h postprandial glucose levels - Halse, Rhiannon; Wallman, K.; Newnham, J.; Guelfi, K. (W.B. Saunders Co., 2013)
Objective To compare the effect of an acute 30-min bout of self-paced stationary cycling (SC) with treadmill walking (TW) or a resting control (CON) on maternal blood glucose, insulin and metabolic responses during pregnancy. Methods Twelve healthy women at 29.9 ± 2.4 (mean ± SD) weeks gestation consumed a 75 g carbohydrate drink as part of an oral glucose tolerance test (OGTT) following 30 min of SC, TW or CON. Blood was sampled before and after exercise, and for 2 h in response to the OGTT for the determination of glucose and insulin. Exercise intensity was monitored and enjoyment of TW and SC was assessed post-exercise. Results Women selectively worked harder in SC compared with TW, with a higher maternal heart rate, rating of perceived exertion, mean oxygen consumption, respiratory exchange ratio, and total energy expenditure during exercise (p < 0.05). SC was also associated with significantly lower postprandial blood glucose levels at 120 min following the OGTT (6.9 ± 0.9 mmol·l - 1 ) compared with both CON (8.1 ± 0.7 mmol·l - 1 , p = 0.001) and TW (7.8 ± 0.9 mmol·l - 1 , p = 0.004) and lower insulin at 120 min post-glucose ingestion compared with TW (p = 0.021). Enjoyment was similar between exercise protocols (p = 0.437). Conclusions In late pregnancy, an acute 30 min bout of self-paced SC may be preferable to a matched duration of TW given the additional energy expenditure that can be achieved, which in turn appears beneficial for blunting the glycemic response to glucose ingestion. © 2013 Elsevier Inc.